Origin and Evolution of Enzymes with MIO Prosthetic Group: Microbial Coevolution After the Mass Extinction Event - Peng, Fei; Engel, Ulrike; Aliyu, Habibu; Rudat, Jens (Frontiers in Genetics, 2022)
After the Late Ordovician mass extinction event, the ancient plants and terrestrial vertebrates were faced with various challenges, especially ultraviolet (UV) light. These stresses have probably resulted in changes in the biosynthetic pathways, which employed the MIO (3,5-dihydro-5-methylidene-4H-imidazole-4-one)-dependent enzymes (ammonia-lyase and aminomutase), leading to enhanced accumulation of metabolites for defense against UV radiation, pathogens, and microorganisms. Up to now, the origin and evolution of genes from this superfamily have not been extensively studied. In this report, we performed an analysis of the phylogenetic relations between the members of the aromatic amino acid MIO-dependent enzymes (AAM), which demonstrated that they most probably have a common evolutionary origin from ancient bacteria. In the early soil environments, numerous bacterial species with tyrosine ammonia-lyase genes (TAL; EC 4.3.1.23) developed the tyrosine aminomutase (TAM; EC 5.4.3.6) activity as a side reaction for competing with their neighbors in the community. These genes also evolved to the other TAL-like enzymes such as histidine ammonia-lyase (HAL, EC 4.3.1.3) and phenylalanine ammonia-lyase (PAL; EC 4.3.1.24) in different bacterial species for metabolite production and accumulation for adaptation to adverse terrestrial environmental conditions. On the other hand, the existence of phenylalanine aminomutase (PAM; EC 5.4.3.10) and phenylalanine/tyrosine ammonia-lyase (PTAL; EC 4.3.1.25) strongly indicates the horizontal gene transfer (HGT) between bacteria, fungi, and plants in symbiotic association after the acquirement of the PAL gene from their ancestor.